Analisis Pelayanan Filipus Sebuah Konsep Teologi Kontekstual Berdasarkan Kisah Para Rasul 8: 4-25 - Ijen Ijen; Polyongkico Polyongkico (Sekolah Tinggi Teologi Simpson Ungaran, 2020)
This scientific work was written by discussing several things as follows: Analysis of Philip's ministry in a contextual theology concept in Acts 8: 4-25, which explains the ministry carried out by Philip in the city of Samaria, Philip is known as a preacher of the gospel, when he succeeded in preaching the gospel in Samaria. In Samaria Philip had to face a sorcerer named Simon, the Samaritans and Philip had to give real teaching in order to be influential and reliable. In this paper the author uses a qualitative method with a literature study approach. Based on the analysis of Philip's ministry, a contextual theological study based on Acts 8: 4-25, the authors found that there were four teachings from Philip's ministry in Samaria, namely giving correct teaching, convincing with miracles, winning people who were influential, not compromising on sin. , and baptize with the Holy Spirit.